Rabies in Nigeria: a new paradigm shift? (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is an infectious disease of the central nervous system (CNS) that kills over 50,000 people each year. The prevalence rate is between 15-20% in Nigeria, however, because of the problem with reporting, the true picture is difficult to obtain. Most of the cases are from the rural areas and are not reported to the relevant authorities. Recent survey of dog brain from dog market across three states showed an increase in the prevalence of rabies up to 54% from Kaduna State, 50 from Abuja while Plateau State had 58% prevalence. In addition, the emergence of asymptomatic rabies which after several mouse inoculations will kill the mice without showing clinical signs of rabies is case of concern. This paper demonstrates the public health significance of the observed high rabies prevalence and the dangers of having asymptomatic rabid dog in the society.